Influence of active control strategies on exhaust thermal management for diesel particular filter active regeneration. (5th June 2017) - Bai, Shuzhan; Chen, Guobin; Sun, Qiang; Wang, Guihua; Li, Guo-xiang
Graphical abstract: This figure shows the exhaust temperature comparison in WHTC transient cycle between using the active control measures in exhaust thermal management and without active control measures. We can conclude, in the 1800 s transient cycle period, exhaust temperature increased completely and effectively, especially in idling condition and low temperature conditions. Exhaust temperature at all time were over 200 °C, with 96% over 220 °C, 78% over 250 °C, the average exhaust temperature of whole cycle increased from 238 °C to 318 °C, increase by 34%, secure the exhaust temperature before DOC capable of match current injection start condition. Highlights: Using the intake throttle to controlling intake air can increase exhaust temperature obviously. The effects of injection pressure and injection advance angle on exhaust temperature is studied. The effects of post injection angle and injection quantity on exhaust temperature is studied. The effects of active control strategies on oxygen concentration in exhaust is studied. Active control strategies can increased exhaust temperature effectively in WHTC transient cycle. Abstract: The control strategies of exhaust thermal management are the premise of achieving the regeneration for Diesel Particulate Filter (DPF). In steady conditions with medium and low load, the effects of active control strategies on exhaust thermal management were studied at the test bench, which include intake throttle valve opening, injection advance angle, injection pressure and post injection. Compared with full opening of intake throttle valve, the 15–20% opening of intake throttle valve could increase the exhaust temperature by about 140 °C, decrease the NOx emission but deteriorated the Particulate matter (PM) emission and fuel consumption. The change of injection advance angle and injection pressure have little effect on the exhaust temperature, but have a great effect on the emissions of NOx, PM and the fuel consumption. Optimized matching of the injection advance angle and quantity of post injections improves the exhaust temperature by about 70 °C. The World Harmonized Transient Cycle (WHTC) was used to evaluate the effect of improving exhaust temperature. WHTC experimental results indicated clearly that the exhaust temperature was effectively increased within the whole 1800 s, especially in the idle and low load conditions.